The Combined Use of Metformin and Methotrexate in Psoriasis Patients with Metabolic Syndrome - Huynh Thi Xuan Tam; Luong Nguyen Dac Thuy; Ngo Minh Vinh; Tran Ngoc Anh; Bui Thi Van (Hindawi Limited, 2022)
Objective. To evaluate the efficacy and safety of the combination of metformin and methotrexate (MTX) versus MTX monotherapy in treating psoriasis in patients with metabolic syndrome. Materials and Methods. A prospective clinical trial was conducted using metformin and MTX to treat psoriasis patients with metabolic syndrome. A treatment group of 35 psoriasis patients with metabolic syndrome was treated with MTX and metformin. A control group of 31 psoriasis patients with metabolic syndrome was treated with MTX only. Results. Patients treated with the combined regimen showed measured improvement in disease status compared to those treated with MTX monotherapy. The Psoriasis Area and Severity Index (PASI) scores of psoriasis patients with metabolic syndrome using the metformin and MTX combination were significantly lower than those treated with MTX only p<0.05. The combination treatment group also showed a significant decrease in blood sugar and triglyceride levels after 3 months p<0.05. However, there were no significant differences in subclinical indexes between the treatment and control groups. Conclusion. In this treatment sample, a combination of metformin and MTX in psoriasis patients with metabolic syndrome showed positive responses and no serious side effects.